2010
DOI: 10.1016/j.ijpharm.2010.03.057
|View full text |Cite
|
Sign up to set email alerts
|

The enhanced aerosol performance of salbutamol from dry powders containing engineered mannitol as excipient

Abstract: The aim of the present study was to investigate the effect of crystallising mannitol from different binary mixtures of acetone/water on the resultant physical properties and to determine the effects of any changes on in vitro aerosolisation performance, when the different mannitol crystals were used as a carrier in dry powder inhaler formulations containing salbutamol sulphate. Mannitol particles were crystallised under controlled conditions by dissolving the sugar in water and precipitating the sugar using bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
63
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 23 publications
5
63
0
Order By: Relevance
“…Its potential use as a carrier for aerosol delivery has been reported (Tee et al, 2000;. Mannitol does not have a reducing sugar function, is less hygroscopic than lactose (Saint-Lorant et al, 2007)and gives a suitable sweet after-taste which has a benefit to patients confirming them that a dose has been properly administered (Kaialy et al, 2010).Mannitol proved to be the most promising candidate for this application than the more hygroscopic sugar alcohols such as sorbitol, xylitol and maltitol. D-mannitol is currently marketed in some countries as a pulmonary diagnostic dry powder inhalation aerosol (Aridol TM ) and as a therapeutic dry powder inhalation aerosol for the treatment of cystic fibrosis and chronic bronchitis (Bronchitol TM ) which are recently approved by US food and drug administration office and a European regulatory committee, respectively (Mansour et al, 2010).Spherical mannitol particles used in Aridol TM were produced by spray drying (Tang et al, 2009).A DPI formulation for inhalation of ciprofloxacin hydrochloride (an antibacterial fluoroquinolone) was prepared by its co-spray drying with different percentages of mannitol.…”
Section: Mannitolmentioning
confidence: 99%
See 1 more Smart Citation
“…Its potential use as a carrier for aerosol delivery has been reported (Tee et al, 2000;. Mannitol does not have a reducing sugar function, is less hygroscopic than lactose (Saint-Lorant et al, 2007)and gives a suitable sweet after-taste which has a benefit to patients confirming them that a dose has been properly administered (Kaialy et al, 2010).Mannitol proved to be the most promising candidate for this application than the more hygroscopic sugar alcohols such as sorbitol, xylitol and maltitol. D-mannitol is currently marketed in some countries as a pulmonary diagnostic dry powder inhalation aerosol (Aridol TM ) and as a therapeutic dry powder inhalation aerosol for the treatment of cystic fibrosis and chronic bronchitis (Bronchitol TM ) which are recently approved by US food and drug administration office and a European regulatory committee, respectively (Mansour et al, 2010).Spherical mannitol particles used in Aridol TM were produced by spray drying (Tang et al, 2009).A DPI formulation for inhalation of ciprofloxacin hydrochloride (an antibacterial fluoroquinolone) was prepared by its co-spray drying with different percentages of mannitol.…”
Section: Mannitolmentioning
confidence: 99%
“…It was also indicated that mannitol particles crystallized from either acetone or ethanol (α-mannitol) showed the best aerosolisation performance while poorest aerosolisation performance was obtained from grounded mannitol (β-mannitol) (Kaialya et al, 2011).The same research group in another study again reported the better inhalation performance of salbutamol sulfate from elongated mannitol. In this study mannitol was crystallized from different binary mixtures of acetone/water and its carrier role in DPI formulations of salbutamol sulfate was investigated (Kaialy et al, 2010).Mannitol particles, produced by spray drying, have been used commercially (Aridol TM ) in bronchial provocation test (mannitol particle itself as an active ingredient not as a carrier). In a study, a confined liquid impinging jets (CLIJs) followed by jet milling was applied and introduced as an alternative method for spray drying.…”
Section: Mannitolmentioning
confidence: 99%
“…In contrast to jet-milling, particles with precisely engineered physical properties were, for instance, engineered using antisolvent crystallization (Kaialy et al, 2014(Kaialy et al, , 2010, batch cooling crystallization (Kaialy et al, 2012), spray drying (Vehring, 2008), spray-freeze drying (Rogers et al, 2003), etc. Freeze-drying (lyophilisation) is a technical procedure that involves the removal of frozen water by sublimation.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] From the stand point of particle shape, the shape with a smaller surface contact area generally results in a higher dispersibility.…”
mentioning
confidence: 99%
“…[14][15][16][17] From the stand point of particle shape, the shape with a smaller surface contact area generally results in a higher dispersibility. 18) The particles prepared by the supercritical fluid antisolvent method presented various shapes as a function of materials and preparation conditions.…”
mentioning
confidence: 99%